Palatal lesions: discriminative value of conventional MRI and diffusion weighted imaging - Yuan, Ying (Br J Radiol, 2016)
OBJECTIVE: To evaluate and compare the ability of conventional MRI, diffusion-weighted imaging (DWI) and a combination of both MRI techniques to differentiate malignant and benign palatal lesions. METHODS: A retrospective review of MRI findings was performed in patients with pathologically confirmed palatal lesions between January 2012 and December 2014. Each lesion was evaluated with conventional MRI characteristics, including enhancement, inner texture, margin, adjacent soft-tissue involvement and cervical lymph node, and/or apparent diffusion coefficient (ADC) value. Statistical analyses were performed to assess the differential performance of each parameter separately and together. RESULTS: A total of 42 patients (24 males, 18 females; age: 54.9 ± 16.4 years) were investigated. The optimal cut-off ADC value to distinguish malignant from benign lesions was 1.02 × 10(−3) mm(2) s(−1), with a sensitivity of 87.5% and a specificity of 75.0%. Conventional MRI showed a sensitivity of 87.1% and a specificity of 63.6%. Combination of conventional MRI and ADC scores increased sensitivity to 100% and specificity to 75.0%. The AUCs did not differ significantly between conventional MRI alone, DWI alone and integration of both. CONCLUSION: Additional DWI does not substantially improve differential ability of conventional MRI. However, combining ADC values with conventional MRI improves both sensitivity and specificity, which is of worth to be further validated in prospective studies with larger sample sizes. ADVANCES IN KNOWLEDGE: Combination of conventional MRI and ADC scores could increase the ability to differentiate malignant from benign palatal lesions, with a sensitivity of 100% and specificity of 75.0%, although without statistical significance.